GERAKAN SOSIAL DALAM UPAYA PERLINDUNGAN ANAK BERBASIS AL-QUR’AN - Derysmono, Derysmono (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2022)
The conclusion of this paper is that the social movement in efforts to protect children based on the Qur'an is realized through four things; first: the integration of child protection, second: child-friendly families, thirdly the role of waqf in child protection, four: optimization of social media. There are three reasons for violence against children, first; parents or family, second; social/community environment, and the three children themselves. So far, the child protection movement has not been implemented optimally, due to the lack of facilities in its implementation, the lack of funding support, and the lack of maximum synergy between families, communities, schools and the government.